Mollusks, Echnioderms, Coelenterates, etc. Part G [electronic resource] : Alcyonaria and Actinaria - Verrill, A. E. (Addison Emery), 1839-1926.; Canadian Arctic Expedition (1913-1918) (Ottawa : F.A. Acland, 1922)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 8, pt. G. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44